Developing a Letter-Ordering Card for Mastering Arabic Vocabulary: تطوير وسيلة بطاقة ترتيب الحروف لإتقان المفردات العربية - Selian, Bagas Nirwana; Salmiyanti, Salmiyanti (Institut Agama Islam Negeri Lhokseumawe, 2025)
Vocabulary mastery is one of the main challenges in learning Arabic at the madrasah level. Therefore, attractive and effective learning media are needed to enhance students’ understanding. This study aims to develop picture card media with letter arrangements as a learning tool for Arabic vocabulary (mufradat) among seventh-grade students at MTsN Lhokseumawe. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research population was 215 students, with a sample of 32 students. Data were collected using expert validated questionnaires and student response questionnaires. The results showed that the picture card media received a score of 91% from media experts (very good category) and 100% from material experts (highly feasible). Student responses were also positive, with a percentage of 89%, indicating that this media is effective, engaging, and feasible for use in Arabic vocabulary learning.